From Deceiving to Believing: Psychological Impact of Deceiving as Resistance against the Patriarchal System in Emi Yagi’s “Diary Of A Void” - Fauzia, Talitha Rizky; Istiani, Imas (Universitas Cokroaminoto Palopo, 2026)
In the novel “Diary Of A Void” written by Emi Yagi, the main character pretends her pregnancy in an effort to resist patriarchal pressure in the workplace. The main objective of this study is to examine the way in which the pretended pregnancy by the main character is an act of rebellion against patriarchal pressure in the workplace and its impact on the mental health of the main character. This research will utilize a qualitative textual analysis approach to explore the themes of resistance and deception in Emi Yagi’s “Diary Of A Void”. In Emi Yagi's “Diary Of A Void”, Shibata fakes a pregnancy to resist patriarchal workplace norms. Exploiting societal privileges for pregnant women, she rejects unfair tasks, forces male colleagues to assume responsibilities, and secures personal time. Her deception disrupts gender dynamics, asserting autonomy in a restrictive, male-dominated environment. The psychological impact of living a lie in the novel is relief and a sense of freedom, isolation and loneliness, the psychological strain of sustaining the lie, transformation in social perception, self-reflection, and existential thoughts.